Performance of InsCor and three international scores in cardiac surgery at Santa Casa de Marília - Tiveron,Marcos Gradim (2015)
Objective: To apply and to compare the Society of Thoracic Surgery score (STS), EuroSCORE (Eurosc1), EuroSCORE II (Eurosc2) and InsCor (IS) for predicting mortality in patients undergoing to coronary artery bypass graft and/or valve surgery at the Santa Casa Marilia. Methods: The present study is a cohort. It is a prospective, observational, analytical and unicentric. We analyzed 562 consecutive patients coronary artery bypass graft and/or valve surgery, between April 2011 and June 2013 at the Santa Casa Marilia. Mortality was calculated for each patient through the scores STS, Eurosc1, Eurosc2 and IS. The calibration was calculated using the Hosmer Lemeshow test and discrimination by ROC curve. Results: The hospital mortality was 4,6%. The calibration is generally adequate group P=0.345, P=0.765, P=0.272 and P=0.062 for STS, Eurosc1, Eurosc2, and IS respectively. The discriminatory power of STS score 0.649 (95% CI 0.529 to 0.770, P=0.012), Eurosc1 0.706 (95% CI 0.589 to 0.823, P ≤0.001), Eurosc2 was 0.704 (95% CI 0.590-0.818 P=0.001) and InsCor 0.739 (95% CI 0.638 to 0.839, P ≤0.001). Conclusion: We can say that overall, the InsCor was the best model, mainly in the discrimination of the sample. The InsCor showed good accuracy, in addition to being effective and easy to apply, especially by using a smaller number of variables compared to the other models.